Circulating and Tumor-Infiltrating Immune Checkpoint-Expressing CD8+ Treg/T Cell Subsets and Their Associations with Disease-Free Survival in Colorectal Cancer Patients - Alhasan Alsalman (14802873) (2022)
T cells in the tumor microenvironment (TME) have diverse roles in anti-tumor immunity, including orchestration of immune responses and anti-tumor cytotoxic attack. However, different T cell subsets may have opposing roles in tumor progression, especially in inflammation-related cancers such as colorectal cancer (CRC). In this study, we phenotypically characterized CD3+CD4- (CD8+) T cells in colorectal tumor tissues (TT), normal colon tissues (NT) and in circulation of CRC patients. We investigated the expression levels of key immune checkpoints (ICs) and Treg-related markers in CD8+ T cells. Importantly, we investigated associations between different tumor-infiltrating CD8+ T cell subpopulations and disease-free survival (DFS) in CRC patients. We found that FoxP3 expression and ICs including PD-1, CTLA-4, TIM-3, and LAG-3 were significantly increased in tumor-infiltrating CD8+ T cells compared with NT and peripheral blood. In the TME, we found that TIM-3 expression was significantly increased in patients with early stages and absent lymphovascular invasion (LVI) compared to patients with advanced stages and LVI. Importantly, we report that high levels of certain circulating CD8+ T cell subsets (TIM-3-expressing, FoxP3−Helios−TIM-3+ and FoxP3−Helios+TIM-3+ cells) in CRC patients were associated with better DFS. Moreover, in the TME, we report that elevated levels of CD25+ and TIM-3+ T cells, and FoxP3+Helios−TIM-3+ Tregs were associated with better DFS. Other Information Published in: Cancers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/cancers14133194